Academic Self-Efficacy and Postgraduate Procrastination: A Moderated Mediation Model - Liu, Guoqing; Cheng, Gang; Hu, Juan; Pan, Yun; Zhao, Shouying (Frontiers in Psychology, 2020)
Abstract：Studies in recent years have shown that academic procrastination in postgraduates is very common and has a negative impact on their mental health. Therefore, we conducted this study to explore the influencing mechanism of postgraduate academic procrastination. In this study, based on the Temporal Decision Model (TDM) of procrastination and the strength model of self-control, we administered a questionnaire survey to 577 full-time postgraduates (351 females, 226 males) to explore the influence mechanisms and gender differences of motivational and volitional factors on academic procrastination. Our results indicated significant differences in academic self-efficacy between females and males. Academic self-efficacy was positively correlated with academic self-control and negatively correlated with academic procrastination; academic self-control was negatively correlated with academic procrastination. Academic self-control had a completely mediating effect in the influence of academic self-efficacy on academic procrastination. Gender variables moderated the influence of academic self-efficacy on academic self-control and thus significantly moderated the mediating effect of academic self-control. Specifically, academic self-control had a stronger mediating effect between academic self-efficacy an d academic procrastination for female postgraduates. Our findings may provide guidance for postgraduates who exhibit academic procrastination and extend the theory of academic procrastination.